Modern analogue foraminiferal census counts of common taxa from shallow water around New Zealand, used for paleo-water depth estimates - Hayward, Bruce William (PANGAEA, 2022)
Relative abundance of common benthic foraminifera taxa in Recent shallow-marine sediment samples from around New Zealand and their tidal elevation or subtidal depths used in modern analogue technique to estimate paleo-water depth of young fossil faunas in many publications by the Geomarine Research group, 2000-2022.
Keywords: Benthic foraminifera; Holocene; Modern Analogue Technique (MAT); New Zealand; Recent